Recent advances in non-alcoholic steatohepatitis-associated hepatocellular carcinoma: immune cells, metabolic dysregulation, and therapeutic strategies - Liu, Lisi; Duan, Xun; Ju, Baozhao (Frontiers in Oncology, 2026)
Non-alcoholic steatohepatitis (NASH), the inflammatory progression of non-alcoholic fatty liver disease (NAFLD), is a leading cause of hepatocellular carcinoma (HCC) amid rising obesity and metabolic syndrome. This review elucidates the immunometabolic interplay driving NASH-HCC pathogenesis. Immune cells, including Kupffer cells, monocyte-derived macrophages, and T-cell subsets, orchestrate chronic inflammation and fibrosis via cytokine cascades (TNF-α, IL-1β, TGF-β1) and polarization shifts. Metabolic dysregulation—including insulin resistance, lipid accumulation, and oxidative stress—exacerbates hepatocyte injury, disrupts the balance between apoptosis and compensatory proliferation, and promotes immune evasion through pathways such as β-catenin/TNFRSF19 signaling and hypoxia-inducible factor 1-alpha (HIF-1α). Gut-liver axis alterations further amplify inflammation. Therapeutic advances include immunotherapies (PD-1 inhibitors combined with anti-angiogenics), metabolic regulators (PPARα/FXR agonists, GLP-1RAs), and lifestyle interventions, though NASH-HCC shows reduced immunotherapy efficacy due to unique immunosuppressive microenvironments. Future directions emphasize novel immune targets (MDSCs, SLAMF1), metabolic reprogramming, and microbiota modulation for precision therapies. Integrating multimodal approaches holds promise for halting NASH-to-HCC progression and improving outcomes.